2012
DOI: 10.1371/journal.pone.0051306
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents EBV Transformation and Inhibits the Outgrowth of EBV-Immortalized Human B Cells

Abstract: BackgroundEpstein Barr virus-associated lymphoproliferative disease is an increasing complication in patients with immunosuppressive conditions. Although the current therapies for this disorder are effective, they are also associated with significant toxicity. In an attempt to identify newer therapeutic agents, this study investigated the effects of Resveratrol, a naturally occurring polyphenolic compound, on the EBV transformation of human B cells.Methodology/Principal FindingsThis study demonstrates that res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The roots of the p olygonum cuspidatum , or Japanese knotweed, contains the highest naturally occurring levels of resveratrol and has been used in traditional Japanese and Chinese medicinal treatments for dermatitis, bacterial infections and inflammation. Plants produce resveratrol in response usually to mechanical injuries, ultraviolet radiation and as a defense for viral and fungal infections [39, 40]. Resveratrol has become the most common phytoalexin currently studied in modern healthcare because of the highly publicized “French Paradox”, an observation that there is a relatively low incidence of cardiovascular disease in France despite a particularly rich saturated-fat diet from the high consumption of red wine [41].…”
Section: Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…The roots of the p olygonum cuspidatum , or Japanese knotweed, contains the highest naturally occurring levels of resveratrol and has been used in traditional Japanese and Chinese medicinal treatments for dermatitis, bacterial infections and inflammation. Plants produce resveratrol in response usually to mechanical injuries, ultraviolet radiation and as a defense for viral and fungal infections [39, 40]. Resveratrol has become the most common phytoalexin currently studied in modern healthcare because of the highly publicized “French Paradox”, an observation that there is a relatively low incidence of cardiovascular disease in France despite a particularly rich saturated-fat diet from the high consumption of red wine [41].…”
Section: Resveratrolmentioning
confidence: 99%
“…Specifically, resveratrol can induce cancer cell apoptosis by interfering with multiple signaling pathways activated in transformed cells [4045]. Clinical trials have also defined the safety, pharmacokinetics and metabolism as both a single synthetic agent and constituent of food at variable doses [46].…”
Section: Resveratrolmentioning
confidence: 99%
“…Another link between miR-155 and EBV transformation was provided by studies on the effect of resveratrol, which blocked the expression of the anti-apoptotic viral gene BHRF1 and down-regulated the anti-apoptotic proteins Mcl-1 and survivin concomitantly with a decrease in the expression of miR-155 and miR-34a in EBV-infected B cells. Therefore, critical steps for EBV transformation and cell survival are prevented [40]. On the basis of these results it was suggested that resveratrol may be a potentially effective therapeutic alternative to prevent EBV-associated lymphoproliferative diseases in immunocompromised patients.…”
Section: Mir-155 and Herpesvirusesmentioning
confidence: 99%
“…In preconditioning cardioprotection, prosurvival Mcl-1 -also a Bcl-2 member -acts in a mechanism with STAT3 and NFkappa B [27]. In the process of oncogenesis this mechanism is mimicked on upregulation of Mcl-1 with NF-kappa B and STAT3 [28].…”
Section: Cardioprotection Against Ischaemia-reperfusion Challengementioning
confidence: 99%
“…i Cancer employs the prosurvival cascade Mcl1/NF-kappa B/STAT3 [28] with the same cascade operating in cardioprotection [27].…”
Section: Cancer Cardioprotectionmentioning
confidence: 99%